Rare bird documentation form for Peregrine Falcon at Tomahawk Marsh, 1994 - Thelen, Edet al (1994)
Rare bird documentation form for a Peregrine Falcon at Tomahawk Marsh in Sac County, IA on September 24, 1994. Epson - sheet feed